Positional accuracy improvement of cadastral record via Angular-Based Adjustment / Nur Fatiha Mohd Nizam - Mohd Nizam, Nur Fatiha (2023)
Malaysia's land records management landscape has been drastically changed with the e-cadastral implementation. The least-square estimation (LSE) that can preserve positional accuracy has taken over the role of Bowditch in systematically distributing the random errors in cadastral measurement. However, the use of bearing that is affected by the propagation of errors in cadastral network adjustment has significantly affected the quality of LSE solutions. Thus, to scrutinize this issue, this study aims to quantify the ability of direct measurement (i.e. angle) to constrain the augmentation of errors that suffered from indirect data (i.e. bearing). The first experiment was designed to measure the ability of LSE in preserving the accuracy of cadastral record. To achieve the research aims, later experiment has performed two (2) sets of LSE adjustments using both data: i. Bearing; and ii. Angle. Three (3) sets of traverse networks were utilized to rigorously evaluate the findings: i. Small; ii. Large; and iii. Combination of small and large. With the RMSE of 0.013m, it is proven that LSE manage to preserve the positional accuracy of land record compared to Bowditch solution, 0.024m. While later experiment demonstrated that direct measurement has significantly improve the quality of cadastral data up to 30%. In contrast, large traverse yield opposite result and further analysis has found that limitation of bearing adjustment that might contribute to adjustment uncertainties. This study reveals that the angular adjustment is able to reduce propagation in cadastral network rather than bearing adjustment which eventually increases the positional accuracy in cadastral database.